Rediscovering Political Friendship : Aristotle's Theory and Modern Identity, Community, and Equality - Ludwig, Paul W. (Cambridge University Press, 2020)
Cover -- Half-title -- Title page -- Copyright information -- Dedication -- Epigraph -- Contents -- Preface and Acknowledgments -- Especially for Theorists -- We All Have a Stake in Theoretical Debates -- People -- Introduction -- The Persistence of Civic Friendship -- Why Study Civic Friendship? -- What Civic Friendship Meant to Aristotle -- Utility -- How People Actually Think -- A Real-World Good -- What Civic Friendship Means for Us -- How Did We Lose the Theory? -- How Would a New Theory Help? -- Would Specific Policies Follow? -- Part I Foundations of Friendship -- 1 Friendship from Identity: Recognizing Anger in the Politics of Recognition -- 1.1 How Identity Theory Came to Seem Accurate (as Well as Healthy) -- 1.2 Is Identity Only a Negating of the Other? -- The Mystery of Personal Identity: Plato's Lysis -- Utility vs. Personal Identity -- Group Identities - Less Mysterious? -- The Negative Approach Clears the Ground -- 1.3 Identity Is Angry: From the Lysis to the Republic and Beyond -- Anger and the Self: The Psychology of the Republic -- 1.4 Anger and Friendship: Aristotle's Politics 7 -- Aristotle's Claim -- Criticizing Republic 2 -- The Anger Is Only Political? -- Explaining Away the Anger -- Other Works of Aristotle Corroborate the Angry Connection -- A Case for ''Irascible'' Friendship -- Conclusion -- 1.5 A Preliminary Result for Identity Politics -- 1.6 Charles Taylor: Where Is the Anger? -- 1.7 Can Liberalism Accommodate the Politics of Recognition? -- Conclusion -- 1.8 What Complicates Liberal Solutions to the Problem of Identity -- 1.9 Conclusion -- 2 Friendships from Utility and Activity: Toward a More Realistic Social Policy (and More Idealistic Civil Society) -- 2.1 Functional Friends -- 2.2 Goodwill: Agents and Spectators -- 2.3 Active Loving, or What Do Friends Do? -- Meeting the Challenge of the Delian Inscription.